Ferroptosis as a mechanism of neurodegeneration in Alzheimer's disease. Issue 5 (9th October 2021) - Jakaria, Md.; Belaidi, Abdel Ali; Bush, Ashley I.; Ayton, Scott
Abstract: Alzheimer's disease (AD) is the most prevalent form of dementia, with complex pathophysiology that is not fully understood. While β‐amyloid plaque and neurofibrillary tangles define the pathology of the disease, the mechanism of neurodegeneration is uncertain. Ferroptosis is an iron‐mediated programmed cell death mechanism characterised by phospholipid peroxidation that has been observed in clinical AD samples. This review will outline the growing molecular and clinical evidence implicating ferroptosis in the pathogenesis of AD, with implications for disease‐modifying therapies. Abstract : Ferroptosis, an iron‐mediated programmed cell death, is a possible mechanism of neuronal cell death in Alzheimer's disease that is propagated by increased PUFAs and labile iron levels and decreased GSH and antioxidant defense. Several risk factors such as stroke and TBI may lead to lipid peroxidation. Iron chelators such as deferiprone and lipophilic antioxidants such as N‐acetylcysteine, Cu II ATSM and vitamin E protect against lipid peroxidation, and they may have potential therapeutic value to prevent ferroptotic stress in the progression of Alzheimer's disease.